THE IMPACT OF ICT IN ADULT AND NON FORMAL EDUCATION IN NIGERIA: A REVIEW - Tukur, Mohammed; Bebeji, Garba Umar; SULEIMAN, Muhammad Muhammad (IJBLE Scientific Publications Community Inc., 2020)
This article is attempting to comprehend the effects of Information and Communication Technology in the exercises of Adult and Non-Formal and Education. It diagrams various techniques to confer training by using Information and Communication Technology (ICT) apparatuses, developments, and arising patterns. Simultaneously, this text features the benefits accumulated by the utilization of Information and Communication Technologies (ICTs) in teaching and learning processes. The effect of Information and Communication Technology on all schooling areas raises difficulties for legislatures, educators and learners. There is a more noteworthy interest for and reception of innovation in training in adult and non-formal education. The realization of the potential of ICTs to improve educational practices is a series of pedagogical and practical challenges. This article considers the issues starting with the basic motivation behind instruction and closes by raising a progression of difficulties that instructive foundations should confront in case they are to effectively coordinate ICT into educating and learning rehearses. The inescapable utilization of ICTs for long-lasting learning just as local area strengthening is a huge pattern in realizing in the current century.